Analisis Penggunaan Media Pembelajaran Berbasis Aplikasi Google untuk Meningkatkan Literasi Digital Siswa Sekolah Dasar di Boyolali : Analysis of the Use of Google Application-Based Learning Media to Improve Digital Literacy of Elementary School Students in Boyolali - Yudha, Fariz Kartika; Utami, Ratnasari Diah (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2024)
The low level of digital literacy in Indonesia needs to be considered by all educational institutions, especially teachers, so that they can intelligently introduce Google-based digital literacy to students. The purpose of this study is to find out the use of google application-based learning media to increase digital literacy. This study uses a descriptive descriptive research approach. The informants in this study were school principals, teachers and students from four schools. Data collection techniques include interviews, observation and documentation. Data analysis in this study used an interactive model consisting of reduction data, presentation data and verification data. To validate the data using source triangulation. The results of the study show that teachers have driven digital literacy by utilizing Google media, namely Google search. Google search media used by teachers is used to find information, material and news that students can understand so that students are used to being able to choose information obtained by elementary school students and information that elementary school-age children cannot know. The teacher also provides videos, both videos downloaded from Google search, namely YouTube and Tik Tok which are used by the teacher, besides that they also use PowerPoint to display material or information.